PESPEKTIF PELAJAR POLITEKNIK TERHADAP TAHAP KESEDIAAN DAN TAHAP KEMAHIRAN PEMBIMBING INDUSTRI DALAM PERLAKSANAAN WORK BASED LEARNING - Mukhtar, N.S.; Ali, A. (Online Journal for TVET Practitioners, 2018)
This study is to examine the level of readiness and skill level of industry mentor in the Work Based Learning (WBL) program. This research have three objective which is the first to identify the level of mentor readiness in the Work Based Learning (WBL) during mentoring process based on the student's perspective on the readiness of educating, the readiness of the management and the willingness to support, the second objective is identifying the level of mentor skills in the Work Based Learning (WBL) during mentoring process based on the students perspective in three element which is communication skills, leadership skills and soft skills application skills to students and the last objective is to identify the differences between perceptions of Polytechnic students on the level of readiness and level of mentor skills in the Work Based Learning (WBL) Program. The students from two polytechnics has been used for this research because they have carried out WBL, there are Polytechnic Sultan Salahuddin Abdul Aziz Shah and Polytechnic Sultan Azlan Shah. This research has used questionnaires as instruments. A total of 103 respondents were selected based on Krejie and Morgan (1970) tables. The data obtained in the analysis uses the mean (descriptive) and inference (independent sample t-test) with the Statistical Package Social Science '(SPSS) Version 16.0.The result show the level of readiness (4.1435) and skill level (4.2149). As a conclusion, the level of readiness and skill level is very important for mentor of WBL’s, to ensure that WBL's objectives and missions will be achieved and run smoothly.